2015
DOI: 10.4254/wjh.v7.i22.2369
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibodies: Principles and applications of immmunodiagnosis and immunotherapy for hepatitis C virus

Abstract: Hepatitis C virus (HCV) is a major health problem worldwide. Early detection of the infection will help better management of the infected cases. The monoclonal antibodies (mAb) of mice are predominantly used for the immunodiagnosis of several viral, bacterial, and parasitic antigens. Serological detection of HCV antigens and antibodies provide simple and rapid methods of detection but lack sensitivity specially in the window phase between the infection and antibody development. Human mAb are used in the immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 137 publications
(143 reference statements)
0
8
0
2
Order By: Relevance
“…Previous studies focused on certain peptide sequences from envelope regions 1 and 2 of HCV as a candidate vaccine. They found that peptide region E1 (aa 315-323) and peptide regions from HCV E2 (aa 412-219) and HCV E2 (aa 517-531) had capability to introduce neutralizing antibodies in mice, rabbits, and goats, while peptide sequence from HCV E2 (aa 430-447) produced nonneutralizing antibodies, which are known interference antibodies [15][16][17][18][19][20][21][22]. Another strategy is to use viral vectors inducing T-cell responses against HCV-infected cells, e.g., adenoviral vectors that have big areas of the HCV genome itself.…”
Section: Hcv Vaccine Strategiesmentioning
confidence: 99%
“…Previous studies focused on certain peptide sequences from envelope regions 1 and 2 of HCV as a candidate vaccine. They found that peptide region E1 (aa 315-323) and peptide regions from HCV E2 (aa 412-219) and HCV E2 (aa 517-531) had capability to introduce neutralizing antibodies in mice, rabbits, and goats, while peptide sequence from HCV E2 (aa 430-447) produced nonneutralizing antibodies, which are known interference antibodies [15][16][17][18][19][20][21][22]. Another strategy is to use viral vectors inducing T-cell responses against HCV-infected cells, e.g., adenoviral vectors that have big areas of the HCV genome itself.…”
Section: Hcv Vaccine Strategiesmentioning
confidence: 99%
“…Согласно МУ 4.2.2787-10 в общей схеме лабораторной диагностики мелиоидоза иммунологическим методам отводится важная роль, особенно при экспресс-анализе поступивших на исследование проб. Для иммунофлуоресцентного и иммуноферментного анализов, а также реакции непрямой агглютинации бактерий применяют современные диагностические препараты и тест-системы, сконструированные с использованием моноклональных антител (МКА) различной эпитопной направленности [11,13,15]. На сегодняшний день широко распространенные иммунодиагностические средства на основе МКА к эпитопам экзополисахарида возбудителя мелиоидоза в той или иной мере характеризуются перекрестной реактивностью в отношении близкородственных непатогенных или малопатогенных буркхольдерий.…”
Section: Introductionunclassified
“…The early generation of neutralizing antibodies has been associated with resistance to infection in individuals at high-risk of exposure, spontaneous clearance during acute infection and sustained virologic response after therapy (Ndongo et al, 2010; Osburn et al, 2014; Swann et al, 2016). Although the envelope of HCV contains multiple immunogenic epitopes, the majority of monoclonal antibodies (mAbs) isolated from infected patients or vaccinated animals have been identified as E2-specific (Tabll et al, 2015). The biological activity of these antibodies is diverse and varies from neutralizing to non-neutralizing or even interfering (Wang et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%